Evolutionary genetics and the major histocompatibility complex of New Zealand robins (Petricidae) : a thesis submitted for the degree of Doctor of Philosophy in Molecular BioSciences at Massey University, New Zealand - Miller, Hilary C. (Massey University, 2003)
The genes of the major histocompatibility complex (MHC) are highly polymorphic and play a direct role in disease resistance. Loss of variation at MHC loci may increase extinction risk in endangered species, due to an inability to combat a range of pathogens. In this thesis, the evolution of class II B MHC genes is investigated, and levels of variation at these loci are measured in two species of New Zealand robin, the endangered Chatham Island black robin (Petroica traversi), and the non-endangered South Island robin (Petroica australis australis). Transcribed class II B MHC loci from both black robin and South Island robin were characterised prior to analysis of MHC variation. To this end, a non-lethal protocol for isolation of transcribed sequences from blood using 3'RACE and RT-PCR was developed. Four class II B cDNA sequences were isolated from black robin, and eight sequences were isolated from the South Island robin, indicating there are at least four class II B loci. RFLP analysis indicated that all class II MHC loci were contained in a single linkage group. Analysis of 3'untranslated region sequences enabled orthologous loci to be identified in the two species, and indicated that multiple rounds of gene duplication have occurred. A partial genomic DNA sequence of a putative pseudogene was also isolated from the black robin. Evolution of MHC genes in New Zealand robins appears to be influenced by gene conversion and balancing selection, resulting in loss of orthologous relationships in the coding region, and a highly diverse peptide-binding region. In order to assess the effect of population bottlenecks on MHC variation, levels of variation in the extant black robin population, which is descended from a single breeding pair, were compared with artificially bottlenecked populations of South Island robin and their respective source populations. Both RFLP and sequence analysis indicated that the black robin is monomorphic at class II B loci, while both source and bottlenecked populations of South Island robin have retained moderate to high levels of variation. Comparison of MHC variation with minisatellite DNA variation in each population indicated that genetic drift was the predominant force determining MHC diversity in bottlenecked populations in the short-term. Despite its lack of MHC variation, the black robin population appears to be viable under existing conditions. The evolutionary history of New Zealand's Petroica species, investigated by phylogenetic analysis of mitochondrial DNA sequences, is also discussed.
Content removed due to copyright: Appendix D: manuscripts 1. Miller, H.C., Lambert, D. M., Millar, C.D., Robertson, B. C., & Minot, E.O. (2003).An evaluation of methods of blood preservation for RT-PCR from endangered species. Conservation Genetics, 4: 651-654 2. Miller, H.C., Lambert, D. M. (2003). Minisatellite DNA profiling detects lineages and parentage in the endangered kakapo (Strigops habroptilus) despite low microsatellite DNA variation. Conservation Genetics, 4: 265-274
Keywords: Endangered birds; Chatham Island robin; South Island robin; Petroica traversi; Petroica australis australis; Robin genetics; Fields of Research::270000 Biological Sciences::270200 Genetics::270203 Population and ecological genetics